Effect of compost tea, streptomycin and cupravit in controlling bacterial leaf blight of rice (Bangladesh Journal of Agricultural Research, 2017)
Compost tea, streptomycin and cupravit were evaluated against the Bacterial Leaf Blight diseases of rice cv. BR11 in two management approaches (preventive and curative) under field condition. The selected cultivar BR11 was cultivated in the field laboratory of the Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh, Bangladesh during the period from July to December 2012. The field experiment was carried out with seven treatments in Randomized Complete Block Design (RCBD) and each was replicated thrice. The treatments were T0 = Control, T1= Compost tea as foliar spray 2 times (preventive) @ 1:5 w/v, T2= Compost tea as foliar spray 2 times (Curative) @ 1:5 w/v, T3 = Streptomycin as foliar spray 2 times (preventive) @1gm/10 L, T4 = Streptomycin as foliar spray 2 times (Curative) @ 1gm/10 L, T5 = Cupravit as foliar spray 2 times (preventive) @ 0.2%, T6 = Cupravit as foliar spray 2 times (Curative) @ 0.2%. Cupravit as foliar spray 2 times (Curative) @ 0.2% showed marked effect in reducing Bacterial Leaf Blight diseases of BR11 rice as well as enhancing yield and yield contributing characters. The effect of compost tea also produced similar effects on disease and yield of rice over control. Among the application options of different treatment, curative application provided better results than preventive under field condition.Bangladesh J. Agril. Res. 42(3): 447-456, September 2017